The Black Heralds: A cry against barbarism - Pachas Almeyda, Miguel (2020)
This text tries to explain that The Black Heralds, the first work of César Vallejo, not only was influenced by the modernist poetry of the time, but had as a fundamental substrate the experiences that César Vallejo lived in a social, econonomic and political context of national and international transcendence.